A Nanostructured Sensor Based on Gold Nanoparticles and Nafion for Determination of Uric Acid - Stozhko, Natalia (Biosensors (Basel), 2018)
The paper discusses the mechanism of uric acid (UA) electrooxidation occurring on the surface of gold nanoparticles. It has been shown that the electrode process is purely electrochemical, uncomplicated with catalytic stages. The nanoeffects observed as the reduction of overvoltage and increased current of UA oxidation have been described. These nanoeffects are determined by the size of particles and do not depend on the method of particle preparation (citrate and “green” synthesis). The findings of these studies have been used to select a modifier for carbon screen-printed electrode (CSPE). It has been stated that CSPE modified with gold nanoparticles (5 nm) and 2.5% Nafion (Nf) may serve as non-enzymatic sensor for UA determination. The combination of the properties of nanoparticles and Nafion as a molecular sieve at the selected pH 5 phosphate buffer solution has significantly improved the resolution of the sensor compared to unmodified CSPE. A nanostructured sensor has demonstrated good selectivity in determining UA in the presence of ascorbic acid. The detection limit of UA is 0.25 μM. A linear calibration curve has been obtained over a range of 0.5–600 μM. The 2.5%Nf/Au(5nm)/CSPE has been successfully applied to determining UA in blood serum and milk samples. The accuracy and reliability of the obtained results have been confirmed by a good correlation with the enzymatic spectrophotometric analysis (R(2) = 0.9938) and the “added−found” technique (recovery close to 100%).